Drug-Based Gold Nanoparticles Overgrowth for Enhanced SPR Biosensing of Doxycycline - Kazmi, Syed Akif Raza (Biosensors (Basel), 2020)
In clinical chemistry, frequent monitoring of drug levels in patients has gained considerable importance because of the benefits of drug monitoring on human health, such as the avoidance of high risk of over dosage or increased therapeutic efficacy. In this work, we demonstrate that the drug doxycycline can act as an Au nanoparticle (doxy-AuNP) growth and capping agent to enhance the response of a surface plasmon resonance (SPR) biosensor for this drug. SPR analysis revealed the high sensitivity of doxy-AuNPs towards the detection of free doxycycline. More specifically, doxy-AuNPs bound with protease-activated receptor-1 (PAR-1) immobilized on the SPR sensing surface yield the response in SPR, which was enhanced following the addition of free doxy (analyte) to the solution of doxy-AuNPs. This biosensor allowed for doxycycline detection at concentrations as low as 7 pM. The study also examined the role of colloidal stability and growth of doxy-AuNPs in relation to the response-enhancement strategy based on doxy-AuNPs. Thus, the doxy-AuNPs-based SPR biosensor is an excellent platform for the detection of doxycycline and demonstrates a new biosensing scheme where the analyte can provide enhancement.